Etuaptmumk: Considering Indigenous Economic Development Through Two-Eyed Seeing - Young, Paula (Université d'Ottawa / University of Ottawa, 2021)
Indigenous economic development is not only about building processes for yielding financial assets. Rather, economic development that advances Indigenous prosperity is about respect for Indigenous legal orders, tradition, culture, distinct history, language, local geographical considerations, and how these are all connected to the attachment to place (land) and traditional territories. In a series of published articles, this portfolio seeks to address critical issues around how to build a more inclusive Canadian economy that advances Indigenous prosperity. The articles critically analyse theoretical perspectives on law and economics; Indigenous economic perspectives; legal decisions and legislation that impact Indigenous peoples legal and economic interests; and asset governance structures in which Indigenous peoples engage. The articles contribute to the legal scholarship involving Indigenous peoples by advancing ways to understand the legal, economic and lived experiences of Indigenous peoples in Canada involved in economic development and working toward reclaiming self-determination. The articles address three key themes that emerged from the research: 1) Eurocentric laws had and continue to have a devastating impact on Indigenous peoples’ legal rights and constrain their economies; 2) Indigenous peoples’ positionality and perspectives must be respected if a pathway is to be built for Indigenous laws to be purposefully included in economic development initiatives that contribute to Indigenous prosperity; and 3) Indigenous ways of knowing exist as living sources of knowledge. The articles are grounded in the Mi’kmaq principle of Etuaptmumk, Two-Eyed Seeing—concerned with engaging multiple perspectives. Two-Eyed Seeing may assist in removing legal constraints by first providing a framework for seeing and understanding some of those constraints imposed by a dominant worldview that does not contemplate various perspectives. Two-Eyed Seeing provides ways to engage with Indigenous legal, sovereign and economic perspectives such that building a more inclusive Canadian economy that advances Indigenous prosperity is possible. Engaging in multiple perspectives will only enrich Canadian society and foster economic reconciliation that benefits all.
Keywords: Indigenous; development